EKSISTENSI RITEL TRADISIONAL PADA PANDEMI COVID-19 - Yuli Sugianti; Onny Fitriana Sitorus (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2021)
This study aims to describe how to maintain the existence of traditional retail businesses during the Covid-19 pandemic. As we all know during this pandemic, all activities were carried out from home, besides that there were several types of businesses that went bankrupt. Then what about traditional retail. The Latifah shop, which is located at Lambangjaya Tambun Selatan, Bekasi Regency, was chosen by the researcher as the research location because there is a match between the current problem and the problem formulation to be investigated. This research uses descriptive research with a qualitative approach. The main data source or informant in this study was the shop owner Latifah and additional informants in the study were shop assistants who helped serve consumers. Data collection methods used were interviews, observation, and documentation. The results of this study indicate that to maintain the existence of a traditional retail store business, several things must be considered, namely 1) good management of simple capital, 2) improving the quality of human resources that are not complex, and 3) changing habits that become obstacles for traditional retailers by evaluating and make innovations in owned shop businesses. Innovation can be done alone or in partnership with other people or institutions who can help manage the store better so that sales continue to increase and the store can continue to grow. By paying attention to this, the shop can maintain its existence in various conditions, for example during this pandemic.